A Closed reduction of chronic protracted bilateral TMJ dislocation using a reduction forcep: case report in a 60-year old woman - Olufemi Ogundipe; Ethelbert Ugwu (Nigerian Dental Association, 2023)
Chronic protracted TMJ dislocation refers to a condition in which the joint is displaced from its articulations and fixated in that position (open-locked) without reduction. The Hippocratic maneuver is usually unsuccessful with a high failure rate making treatment of this condition very challenging. This article reported a case of TMJ dislocation not amenable to the traditional closed reduction method but which was successfully treated using the direct application of reduction forceps on the angle of the mandible. The technical aspects of the procedure and post-operative management were also highlighted.